P08.13 What can probability surveys tell us about changes in chlamydia prevalence in britain? evidence from the national surveys of sexual attitudes and lifestyles (natsal). (13th September 2015) - Woodhall, SC; Soldan, K; Sonnenberg, P; Mercer, CH; Clifton, S; Saunders, P; da Silva, F Coelho; Alexander, S; Tanton, C; Field, N; Copas, A; Ison, CA; et al.
Abstract : Introduction: The National Surveys of Sexual Attitudes and Lifestyles (Natsal) estimated the prevalence of Chlamydia trachomatis (chlamydia) among the sexually-experienced British population in 1999–2001 (Natsal-2) and 2010–12 (Natsal-3). Chlamydia testing among young adults increased substantially between these years, partly due to the introduction of the English National Chlamydia Screening Programme, which achieved national implementation in 2008. We explored what these data might tell us about changing chlamydia prevalence among young adults over the last decade. Methods: We compared estimated chlamydia prevalence among sexually-experienced 18–24 year old men and women between Natsal-2 (n = 680) and Natsal-3 (n = 1, 511). We carried out a sensitivity analysis which accounted for differences in the accuracy of the urine collection procedure and assay used in Natsal-2 (standard universal tube for urine collection; ligase chain reaction) and Natsal-3 (FirstBurst urine collection device; AptimaCombo2). Results: There was no significant difference between the chlamydia prevalence estimates for 18 to 24 year olds in Natsal-3 vs Natsal-2: for men, 2.6% (95% CI: 1.7%–4.0%) vs 2.9% (1.3%–6.3%); OR: 0.91 (0.36–2.27); for women, 3.2% (2.2%–4.6%) vs 3.1% (1.8%–5.2%); OR 1.04 (0.53–2.01). The test-adjusted chlamydia prevalence estimate was slightly lower than the reported prevalence in Natsal-2 among men (2.2% (95% CI, 0.4%–6.1%)) and women (2.5% (1.0%–4.9%)), due to the dominance of specificity error in a low prevalence population. However, there remained no statistically significant difference between surveys. Conclusion: Given the wide confidence intervals on prevalence estimates, the Natsal surveys are consistent with prevalence among sexually-experienced young adults in 2009–2012 being as little as half, or as much as double that in 1999–2001. Even large, national, population-based surveys face limitations in statistical power to detect moderate changes in population prevalence of chlamydia. Analyses of testing uptake, diagnoses rates and prevalence by the rich behavioural data in the Natsal surveys can contribute more to evaluation of chlamydia control. Disclosure of interest statement: Natsal-3 is collaboration between University College London (London, UK), the London School of Hygiene and Tropical Medicine (London, UK), NatCen Social Research, Public Health England (formerly the Health Protection Agency) and the University of Manchester (Manchester, UK). The study was supported by grants from the Medical Research Council and the Wellcome Trust, with contributions from the Economic and Social Research Council and Department of Health.